Wopko Jensma: A Monograph : The Interface between Poetry and Schizophrenia - Sheik, Ayub, (African Literatures in English ;, 2024)
Wopko Jensma's poetry constitutes an interesting and idiosyncratic response to the strife and turmoil in South Africa in the seventies. Jensma's experimental poetry harnesses the signatures of jazz lyrics, concrete poetry, the avant-garde as well as African dance forms in bizarre cameos of underclass misery and racial oppression. In lieu of metrical regularity and rhyme, the aesthetic experience is simulated by asemantic qualities of speech, sound, and rhythmic undulations in what is best described as a "withdrawal of semantic crutches". Jensma's private idiomatic language, mixing of dialects, the use of syncopation, ellipsis, and experimental topography have no doubt contributed to the cryptic and arcane aberrations associated with schizophrenia. This is the first study that explores the link between Jenma's poetry and schizophrenia and in which image, diction, and story coalesce to voice the anguish and alienation of underclass suffering.